A study of Sudden Commencements of Geomagnetic Storms at Trivandrum (MAUSAM, 1969)
The occurrence frequency distribution of SC (+) is not showing any siginifiacnt variation with local time, while the SC(-+) cases occur, in the equatorial station Trivandurm, during the day-time electrojet. There is a direct relationship between the severity of the SC storm and the rate of filed change of the SC amplitude and rise time. At this station, the polarization of the SC field vector in the horizontal plane is linear.